2021
DOI: 10.2147/ppa.s309186
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions and attitude towards MRI safety in Asir Region, Saudi Arabia

Abstract: Purpose To assess the knowledge and attitudes of Saudi patients toward the safety of magnetic resonance imaging (MRI). Methods A cross-sectional study was conducted on 142 Saudi patients at King Khalid hospital, Asir, Saudi Arabia. Data were collected using a self-questionnaire based on MRI safety issues gained from the literature. The questionnaire was divided into two sections, one containing the respondents’ sociodemographic information and the other assessing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
5
2
Order By: Relevance
“…They were found that out of 142 patients, 27 (19%) patients were aware about preparation yourself before MRI while 115 (81%) didn't aware because the literacy rate. 5 In this study total 8% patients aware from MRI zone that is totally different from the study conducted by Magbool et al that were 70.4% knew about the MRI zone because in their doctor or technician explain them. 5 In this study around 42% responded that MRI is safe for pregnant women while 17 responded it's not and rest patients didn't answer but, in the study, conducted by Magbool and et al only 19.7% said that MRI is safe rest patients said it's not.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…They were found that out of 142 patients, 27 (19%) patients were aware about preparation yourself before MRI while 115 (81%) didn't aware because the literacy rate. 5 In this study total 8% patients aware from MRI zone that is totally different from the study conducted by Magbool et al that were 70.4% knew about the MRI zone because in their doctor or technician explain them. 5 In this study around 42% responded that MRI is safe for pregnant women while 17 responded it's not and rest patients didn't answer but, in the study, conducted by Magbool and et al only 19.7% said that MRI is safe rest patients said it's not.…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, as MRI technology continues to evolve and improve, it is essential to keep patients informed about the latest safety protocols and developments in MRI procedures. 5 Patients' knowledge and perception of MRI safety are important factors that can affect their decision to undergo the procedure and their compliance with safety guidelines. Therefore, it is essential for healthcare providers to ensure that patients have a clear understanding of the risks and benefits associated with MRI and to provide appropriate information and support to help them make informed decisions about their healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…This disparity may be explained by social norms, culture, and behavioural paradigms. 15 Despite the expectation that previous experience would grant patients sufficient information about the MRI process and safety issues, this assumption is incorrect. Previous experience with MRI led to two possible scenarios.…”
Section: Sources Of Information and Previous Mri Experiencementioning
confidence: 99%
“…A previous study found that providing detailed information and instructions about the procedure lowered the degree of anxiety among patients [4]. Furthermore, poor knowledge of MRI among patients was reported in a recent study [12]. Therefore, since 73.9% of our participants stated a need for more precise information, we highly recommend providing adequate information, and appropriate answers and instructions for patients to help them control their fear and anxiety throughout the procedure.…”
Section: Discussionmentioning
confidence: 85%